Private Cloud Storage dengan Owncloud 9.1.1 pada Linux Debian 8.6 dan Remote VPN pada Mikrotik RB 750 di SMP Negeri 20 Surakarta - Senoadi, Indriawan, Bana Handaga, S.T.,M.T.,P.h.D (2017)
Cloud computing technology is a technology that is growing but the technology has not been widely used in the field of education. Cloud storage is a technology development of cloud computing technology. Basically SMP Negeri 20 Surakarta not use these technologies to store important files on the activities of the school and still use the flash media to store important files, but the media is dangerous if installed on the affected computer viruses that can delete important files such. Viewed from the above problems, this study will try to create a centralized data storage system using software ownCloud is expected to minimize the use of flash for data sharing and storing important files into the media in order to avoid the spread of the virus. Results from this study is a centralized data storage system called Mediashare and can be accessed using a Personal Computer, Laptop, Android smartphones through a Virtual Private Network. Testing of the system is done through three phases, namely testing simulations using a piece of software that will access the user 51 Mediashare system to determine the robustness of the system server Mediashare. The second stage is to test the system Mediashare directly with 11 teachers of SMP Negeri 20 Surakarta to determine the ease and benefits of such a system. The last stage is to test the security of the server software Mediashare with Zenmap and Havij through spec laptop 4700HQ Processor Intel Core i7, 4GB DDR3 RAM, and a 1TB hard drive